Investigation of Nagashima‐type palmoplantar keratoderma in China: A cross‐sectional study of 234 patients. Issue 3 (1st November 2022) - Liu, Juan; Chen, Zhiming; Hu, Linghan; Song, Zhongya; Mo, Ran; Tsang, Lemuel Shui‐Lun; Liu, Yihe; Huang, Xin; Gong, Zhuoqing; Lin, Zhimiao; Yang, Yong
Abstract: Nagashima‐type palmoplantar keratoderma (NPPK) is the most prevalent hereditary palmoplantar keratoderma (PPK) in China, but there is a paucity of epidemiological data on the Chinese population. To explore the clinical and genetic characteristics, evaluate the demographic distribution, and estimate the burden of disease of NPPK. A total of 234 Chinese patients with NPPK were enrolled from two medical centers and an online PPK support group. Next‐generation sequencing and Sanger sequencing were performed to screen out and confirm pathogenic mutations in SERPINB7 . Clinical features and quality of life (QOL) were evaluated using self‐completed questionnaires. In total, 14 pathogenic mutations were identified in SERPINB7 from the cohort. The top four recurrent mutations were c.796C>T (355, 75.9%), c.522dupT (66, 14.1%), c.650_653delCTGT (24, 5.1%), and c.455G>T (12, 2.6%), accounting for 97.6% of Chinese NPPK patients. Other mutations (11, 2.4%) include c.455‐1G>T, c.336+2T>G, c.635delG and seven novel mutations c.2T>C, c.434delG, c.455‐16A>G, c.656T>C, c.745‐553T>G, c.832C>T, c.1036G>T. The estimated prevalence of NPPK in China was found to be 0.975/10 000 based on Chinese databases. Clinically, there were no apparent genotype–phenotype correlations in NPPK patients. Pediatric patients mainly presented with palmoplantar peeling, while adults presented with scale ( p < 0.001). The most common comorbidities in NPPK patients were onychomycosis (40.0%), eczema (36.8%), and tinea pedis (30.3%). As for burden of disease, NPPK patients' QOL was decreased by a moderate degree. In this study, pathogenic mutations' allele frequencies in SERPINB7 were updated, and prevalence of NPPK in China was estimated. This large‐scale cohort study provides evidence‐based recommendations for patient management. Identification of new mutations are important for timely diagnosis of NPPK. Palmoplantar peeling in children can be used as a hallmark for early recognition of NPPK.